2019
DOI: 10.4014/jmb.1905.05034
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Balanced Microalgal Wastewater Treatment (COD, N, and P) by Interval Inoculation of Activated Sludge

Abstract: Although chemical oxygen demand (COD) is an important issue for wastewater treatment, COD reduction with microalgae has been less studied compared to nitrogen or phosphorus removal. COD removal is not efficient in conventional wastewater treatment using microalgae, because the algae release organic compounds, thereby finally increasing the COD level. This study focused on enhancing COD removal and meeting the effluent standard for discharge by optimizing sludge inoculation timing, which was an important factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 30 publications
2
12
0
1
Order By: Relevance
“…Increased organic matter in wastewater treatment using microalgae is a notorious issue. 44 The dissolved organic matter in Co-MM was significantly lower than in the single culture of microalgae (Figure 5b). The 3D-EEM shows that this is mainly due to the reduction of humic acid-like substances (Figure S7).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Increased organic matter in wastewater treatment using microalgae is a notorious issue. 44 The dissolved organic matter in Co-MM was significantly lower than in the single culture of microalgae (Figure 5b). The 3D-EEM shows that this is mainly due to the reduction of humic acid-like substances (Figure S7).…”
Section: Resultsmentioning
confidence: 92%
“…Increased organic matter in wastewater treatment using microalgae is a notorious issue . The dissolved organic matter in Co-MM was significantly lower than in the single culture of microalgae (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the achieved final concentration of phosphate is below the acceptable level of the surface water quality standard (1 P-mgL -1 ). (China, 2002) Chemical oxygen demand (COD) has been reported as the most challenging problem in the treatment process due to its re-increasing in the wastewater (Lee et al, 2019). As illustrated in Fig 6d, the COD was eliminated gradually from 211 to 50.7 mgL -1 resulted in 76.3% removal rate of COD during 10 days cultivation of C. sorokiniana pa.91 in the photobioreactor.…”
Section: Nutrient Removal Efficiency Of C Sorokiniana Pa91 In the Pmentioning
confidence: 96%
“…wastewater treatment as it is an indicative measure of the organic load (strength of the effluent) in the wastewater and the amount of molecular oxygen that can be consumed for its oxidation (Lee et al, 2019;Otondo et al, 2018). Nonetheless, the fate of COD during microalgal based wastewater treatment procedures have not been well established when compared to other common nutrients such as nitrogen and phosphorus (Choi & Lee, 2012;Lee et al, 2019). In this study, the concentration of COD was found to decrease in both ADMC and ADAE from Day 0 to Day 7 (Table 3).…”
Section: Chemical Oxygen Demand (Cod) Represents Another Important Pa...mentioning
confidence: 99%